Influence of birth weight on differences in infant mortality by social class and legitimacy. Issue 6808 (19th October 1991) - Leon, D A
Abstract : OBJECTIVE–To investigate the influence of birth weight on the pronounced social class differences in infant mortality in Britain. DESIGN–Analysis of routine data on births and infant deaths. SETTING–England and Wales. SUBJECTS–All live births and infant deaths, 1983-5. MAIN OUTCOME MEASURE–Mortality in infants by social class, birth weight, and legitimacy according to birth and death certificates. RESULTS–Neonatal and postneonatal mortality (deaths/1000 births) increased with social class. Neonatal and postneonatal mortality was 4.2/1000 and 2.3/1000 respectively for social class I and 6.8/1000 and 5.6/1000 respectively for social class V. Mortality was lower among births registered within marriage (postneonatal 3.5/1000; neonatal 5.2/1000) than among those jointly registered outside marriage (5.1/1000; 6.4/1000); mortality was highest in those solely registered outside marriage (7.2/1000; 7.0/1000). For neonatal mortality the effect of social class varied with birth weight. Social class had little effect on neonatal mortality in low birthweight babies and increasing effect in heavier babies. For postneonatal mortality the effect of social class was similar for all birth weights and was almost as steep as for all birth weights combined. CONCLUSION–Birth weight mediates little of the effect of social class on postneonatal mortality.